Learning Models in Sharia Economic Department in Forming Student Career Options in the Sharia Financial Industry - Rumasukun, Muhammad Alfan; Nugraha, Ahmad Lukman (AL-IKTISAB: Journal of Islamic Economic Law, 2021)
This study identifies a learning model in the sharia economics department in shaping student career choices in the sharia finance industry. This research was conducted at the State Islamic Institute Campus, Ponorogo East Java. This research was conducted because the number of workers in the sharia finance industry, especially those who have Islamic economic scientific competence, has decreased. On the other hand, conditions in the sharia financial industry and sharia financial institutions have developed quite rapidly. Likewise, interest in sharia economics at various Islamic religious universities continues to increase. This type of research uses descriptive research methods equipped with qualitative and quantitative data, both primary and secondary data. This study uses a Likert scale to determine the results of the study. The independent variable analysis uses Theory of Planned Behavior, while the dependent variable uses Social Cognitive Career Theory (SCCT). The purpose of this study is to determine the learning model in the Islamic economics department in shaping student career choices in the sharia finance industry. The results of this study indicate an increase in the number of sharia financial institutions, enthusiasts of the Islamic economics major after market demand and special attention from the government with its various incentive policies, but there is a decline in student career choices in the sharia finance industry. The conclusion of this study shows that the decline in student career choices in the sharia finance industry is caused by many factors. In order to provide solutions to the above problems, efforts to improve several designs or learning models on campus need to be improved and enhanced. The most dominant learning model with a percentage of 83.5% is the integration model of religious and general sciences. Next followed by the supervisory teacher motivation intensity model with a percentage of 86.4%.